Pengaruh Transfer Pricing dan Capital Intensity terhadap Tax Avoidance Pada Perusahaan Food & Beverage Yang Terdaftar di BEI Periode 2020-2021 - Laurentya, Valenta; Gouwtama, Chanza Mudita; Tallane, S.E., M.Acc., Yoan Yohana (Universitas Sam Ratulangi, 2023)
his study aims to determine the effect of transfer pricing and capital intensity on tax avoidance. The type of this study used quantitative study with secondary data. The data used in this research are the annual financial reports of manufacturing companies operating in the food and beverage industry during the 2020-2021 period. The data analysis methods used in this research include descriptive statistical tests, classical assumption tests, multiple regression tests and hypothesis tests. The number of samples studied was 38 companies. The results of the research show that transfer pricing and capital intensity do not have a positive effect on tax avoidance.Keywords : Transfer Pricing, Capital Intensity, Tax Avoidance